SLC7A11, a Potential Therapeutic Target Through Induced Ferroptosis in Colon Adenocarcinoma - Cheng, Xin; Wang, Yadong; Liu, Liangchao; Lv, Chenggang; Liu, Can; Xu, Jingyun (Frontiers in Molecular Biosciences, 2022)
Background: Ferroptosis induced by SLC7A11 has important translational value in the treatment of cancers. However, the mechanism of SLC7A11 in the pathogenesis of colonic adenocarcinoma (COAD) is rarely studied in detail. Methods: SLC7A11 expression was explored with The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO) databases and Western blot assay. The correlation of SLC7A11 expression with the abundance of infiltrating immune cells were evaluated via TIMER database. The relation of SLC7A11 expression with immune cell markers was investigated via The Gene Expression Profiling Interactive Analysis (GEPIA). The co-expression genes of SLC7A11 were screened by R packages, and the PPI was constructed via STRING database. SLC7A11 and co-expressed gene modulators were selected by NetworkAnalyst and DSigDB database. The correlations between SLC7A11 and cancer immune characteristics were analyzed via the TIMER and TISIDB databases. Results: SLC7A11 is overexpressed in most tumors, including COAD. The expression level of SLC7A11 has a significant correlation with the infiltration levels of CD8+ T cells, neutrophils, and dendritic cells in COAD. The infiltrated lymphocyte markers of Th1 cell such as TBX21, IL12RB2, IL27RA, STAT1, and IFN-γ were strongly correlated with SLC7A11 expression. Five hub genes co-expressed with SLC7A11 that induce ferroptosis were identified, and mir-335-5p, RELA, and securinine have regulatory effects on it. SLC7A11 was negatively correlated with the expression of chemokines and chemokine receptors, such as CCL17, CCL19, CCL22, CCL23, CXCL14, CCR10, CX3CR1, and CXCR3, in COAD. Conclusion: SLC7A11 may play a role in induced ferroptosis and regulating tumor immunity, which can be considered as potential therapeutic targets in COAD.